Transfer of Dicamba Tolerance from Sinapis arvensis to Brassica napus via Embryo Rescue and Recurrent Backcross Breeding - Jugulam, M. (PLoS One, 2015)
Auxinic herbicides (e.g. dicamba) are extensively used in agriculture to selectively control broadleaf weeds. Although cultivated species of Brassicaceae (e.g. Canola) are susceptible to auxinic herbicides, some biotypes of Sinapis arvensis (wild mustard) were found dicamba resistant in Canada. In this research, dicamba tolerance from wild mustard was introgressed into canola through embryo rescue followed by conventional breeding. Intergeneric hybrids between S. arvensis (2n = 18) and B. napus (2n = 38) were produced through embryo rescue. Embryo formation and hybrid plant regeneration was achieved. Transfer of dicamba tolerance from S. arvensis into the hybrid plants was determined by molecular analysis and at the whole plant level. Dicamba tolerance was introgressed into B. napus by backcrossing for seven generations. Homozygous dicamba-tolerant B. napus lines were identified. The ploidy of the hybrid progeny was assessed by flow cytometry. Finally, introgression of the piece of DNA possibly containing the dicamba tolerance gene into B. napus was confirmed using florescence in situ hybridization (FISH). This research demonstrates for the first time stable introgression of dicamba tolerance from S. arvensis into B. napus via in vitro embryo rescue followed by repeated backcross breeding. Creation of dicamba-tolerant B. napus varieties by this approach may have potential to provide options to growers to choose a desirable herbicide-tolerant technology. Furthermore, adoption of such technology facilitates effective weed control, less tillage, and possibly minimize evolution of herbicide resistant weeds.